Measurements of the hydrodynamic pressure on a surfboard fin during surfing - Stefan Kniesburges; Nina Punger; Bogac Tur; Michael Zöllner; Marc in het Panhuis; Michael Döllinger (Scientific Reports)
Abstract The popularity of surfing has increased during the last 20 years with the growing number of river waves and artificial wave pools. For these different surfing conditions, hydrodynamic characteristics of boards and fins and their optimization become interesting for industry and science to analyze the biomechanics and physiology during surfing. In this work, a measuring system was developed assembled of four small pressure sensors included in a 3D-printed fin within a 2-fin configuration. The measurements were controlled by an acquisition board mounted into a surfboard. The system was initially tested in a water tank and exhibited a high accuracy of measured pressure. Afterwards, a surfer surfed the instrumented surfboard on a river wave and performed three cycles of surfing from one side of the wave channel to the other. The results showed a pressure difference between both sides of the instrumented fin that produces periodical lift forces directed away from the surfboard. Thereby, the maximum lift force was produced during the surfer’s motion from one side of the channel side to the other. It is assumed to increase the stability of the surfer’s back foot in combination with the right fin producing a lift force in opposite direction.